HLA-A, B (Class I) and HLA-DR, DQ (Class II) Antigens in Turkish Patients with Recurrent Aphthous Ulceration and Behçet's Disease - Pekiner, Filiz Namdar; Aytugar, Emre; Demirel, Gülderen Yanikkaya; Borahan, M. Oğuz (Medical principles and practice, 2013)
Objective: The aims of the present study were to typify the human leukocyte antigen system (HLA)-A, B (class I) and HLA-DR, DQ (class II) antigens and to assess the frequency of the presence of these antigens in the Turkish population with recurrent aphthous ulceration (RAU) and Behçet's disease (BD) compared to healthy subjects. Subjects and Methods: Thirty patients with RAU, 30 with BD, and 15 healthy subjects were included in the study. HLA typing was performed by serology with commercial kits for HLA class I and II (One Lambda, Canoga Park, Calif., USA). Results: The HLA-A23 frequency was 26.7% in the RAU patients, which was significantly higher than the 3.3% frequency in the patients with BD (p < 0.05). The HLA-A24 frequency was 33.3% in the RAU patient group, which was significantly higher (p < 0.05) than the frequency in the healthy subjects (6.7%). Significantly higher frequencies (46.7%) of HLA-A30 were found in the healthy subjects compared to the BD (13.3%) and RAU (3.3%) patients (p < 0.05 and p < 0.01, respectively). A higher frequency of HLA-B13 was observed in the RAU (23.3%) patients compared to the BD (0%) patients (p < 0.01). A decrease was observed in HLA-DR10 and HLA-DR17 in the RAU patients (p < 0.05), while a higher frequency of HLA-DR10 was observed in the BD patients compared to the RAU patients (p < 0.01). Conclusions: These results showed that RAU and BD were not in the same spectrum and the involvement of other genetic and/or environmental factors might be responsible for the development of these diseases and/or disease progression.